Sorptive Interactions of Fungicidal 2-(4'-Thiazolyl) Benzimidazole with Soils of Divergent Physicochemical Composition: Sorptive Interactions of Fungicidal 2-(4'-Thiazolyl) Benzimidazole with Soils of Divergent Physicochemical Composition - Ali, Mehtabidah; Jaffri, Shaan Bibi; Ahmad, Khuram Shahzad; Iqbal, Shahid (International Journal of Economic and Environmental Geology, 2019)
Thiabendazole, 2-(4'-thiazolyl) Benzimidazole fungicide is rampantly used in Pakistan for controlling fungal growth in addition to combating various fungus driven diseases. Thiabendazole leaching and mobility patterns can be easily predicted through investigation of Thiabendazole adsorption and desorption behavior in soils. Present work is carried out by conducting a batch equilibration experiment for evaluation of Thiabendazole adsorption and desorption in soils from four diverse Pakistani climatological regions. Data revealed Thiabendazole had moderate to weak adsorption in selected soils with distribution co-efficient Kd(ads) ranging from 13.33 to 24.04 µg/ml in selected soils. The TBZ adsorption in soils best fitted with Freundlich model (R2>0.87). The Freundlich adsorption coefficient (Kf(ads)) values ranged from 4.51 to 8.90 µg/ml. Thiabendazole adsorption trends in the selected soils were positively influenced by the clay content and soil organic matter while it was negatively influenced by soils’ pH. The Freundlich desorption coefficient (Kf(des)) values spanned over a range of 1.03 to 6.43 µg/ml indicating decreased desorption from soils with creditable affinities for Thiabendazole adsorption. The adsorptive interactions between Thiabendazole and selected soils were primarily physical confirmed through lower values of Gibbs free energy ∆G ≤ - 40kJ/mol. Thiabendazole desorption was highly hysterical in all soils with profound irreversibility. Thiabendazole possessed medium mobility patterns in selected soils. The lower adsorptive capability of Thiabendazole in selected soils points towards its lower application rates for combating long term environmentally perilous implications.